Avaliação do potencial anticárie de lectinas vegetais - Teixeira, Edson Holanda (2005)
During the past few deeades has been established a great advanee related to the etiology and dental earie prevention. However, epidemiologie data have demonstrated that it continues to be the most prevalent disease among ali others in odontology. One important etiologie faetor for this disease is the formation of a pathogenie baeteria biofilm that adheres to the dental surfaee, produeing aeids that lead to dental enamel demineralization. These baeteria not adhere direetly to dental enamel surface , but bind to a thin non eellular layer composed by saliva proteins and other maeromoleeules that reeover dental surfaee, this layer is named aequired pelliele. Bactéria interaet with this layer through several speeifie meehanisms and the leetinie interaetion is one of them. Leetins are proteins from non-immune origin that have at least one non-eatalitie domain whieh binds reversibly to speeifie carbohydrates. Sacterial adherenee involves adhesins loeated in the baeteria surfaee and pelliele reeeptors. This thesis aimed to evaluate the possible anti cariogenie potential of leetins extraeted from Cana valia brasiliensis, Dioclea violacea, Lonchocarpus seríceus and Vaitarea macrocarpa seeds and from red marine algae Bryothamnion seaforthii and Bryothamnion triquetrum. The results show that leetins are able to interaet with the aequired pelliele and that algae leetins are the ones among ali tested whieh have the stronger interaetion. In the baeteria adhesion inhibition assay its been verified that the leetins tested are effeetive against the following strains: Streptococcus mutans, S.sobrinus, S.sanguis, S.oralis and S.mitis. Leetins from Cana valia ensiformis, C.brasiliensis, Dioclea violacea, Lonchocarpus sericeus and Vatairea macrocarpa seeds were also able to make the S.mutans eolony forming units not viable, after having a previous eontaet before the ineubation. The results found point out to a great anti earies potential of these moleeules, giving subsides to a possible use as tools in earbohydrate eharaeterization of the aequired pellicle and in prophylaxis, sinee they aet through two meehanisms potentially effeetive: inhibiting baeteria adherenee to the aequired pellicle and antibaeterial effeet. At last, the present work indieates that further studies are needed with emphasis in whieh one of the leetins; these studies should use other biofilm models (that may retraet beUer the mouth environment), "in vivo" experimentation, leetins eytotoxieity assays and the development of a protoeol for human use. These assays are fundamental to allow the use of one or more of these proteins in produets that prevent earies and periodontal disease.